Comics and Sacred Texts : Reimagining Religion and Graphic Narratives - Koltun-Fromm, Ken; Gamzou, Assaf, 1984- (Book collections on Project MUSE., 2018)
"Comics and Sacred Texts explores how comics and notions of the sacred interweave new modes of seeing and understanding the sacral. Comics and graphic narratives help readers see religion in the everyday and in depictions of God, in transfigured, heroic selves as much as in the lives of saints and the meters of holy languages. Coeditors Ken Koltun-Fromm and Assaf Gamzou reveal the graphic character of sacred narratives, imagining new vistas for both comics and religious texts. In both visual and linguistic forms, graphic narratives reveal representational strategies to encounter the sacred in all its ambivalence. Through close readings and critical inquiry, these essays contemplate the intersections between religion and comics in ways that critically expand our ability to think about religious landscapes, rhetorical practices, pictorial representation, and the everyday experiences of the uncanny. Organized into four sections--Seeing the Sacred in Comics; Reimagining Sacred Texts through Comics; Transfigured Comic Selves, Monsters, and the Body; and The Everyday Sacred in Comics--the essays explore comics and graphic novels ranging from Craig Thompson's Habibi and Marvel's X-Men and Captain America to graphic adaptions of religious texts such as 1 Samuel and the Gospel of Mark. Sacred Texts and Comics shows how claims to the sacred are nourished and concealed in comic narratives. Covering many religions, not only Christianity and Judaism, this rare volume contests the profane/sacred divide and establishes the import of comics and graphic narratives in disclosing the presence of the sacred in everyday human experience."--Provided by publisher.